2003
DOI: 10.1177/112067210301300404
|View full text |Cite
|
Sign up to set email alerts
|

Impression Cytology and Ocular Characteristics in Ocular Rosacea

Abstract: Patients with ocular rosacea not only had decreased tear production but also tear instability. Ocular surface epithelium had significant degeneration in patients compared with normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
3
15
0
1
Order By: Relevance
“…The meibomian gland dysfunction and tear component alterations found in adult ocular rosacea often present with conjunctivitis, blepharitis, sties, and chalazia. 8,10 Fully developed rosacea and ocular rosacea are rare in childhood, 22,23 but sties, conjunctivitis, blepharitis, and chalazia are common in children from infancy on. If these eye findings in children have the same pathophysiologic basis as their counterparts in adults, children who present with these conditions might be at increased risk for development of rosacea as adults.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The meibomian gland dysfunction and tear component alterations found in adult ocular rosacea often present with conjunctivitis, blepharitis, sties, and chalazia. 8,10 Fully developed rosacea and ocular rosacea are rare in childhood, 22,23 but sties, conjunctivitis, blepharitis, and chalazia are common in children from infancy on. If these eye findings in children have the same pathophysiologic basis as their counterparts in adults, children who present with these conditions might be at increased risk for development of rosacea as adults.…”
mentioning
confidence: 98%
“…4 The most common clinical findings in ocular rosacea have been reported as telangiectasia and irregularity of the lid margins, meibomian gland dysfunction, blepharitis, papillary hypertrophy, and conjunctival hyperemia. [5][6][7][8][9] Decreased tear volume and tear stability (tear breakup time) have been found to be directly related to the severity of ocular rosacea. 10 Epidemiologic studies suggest that facial and ocular rosacea are part of a continuum.…”
mentioning
confidence: 99%
“…The diagnosis of rosacea remains mainly clinical, though certain investigations such as impression cytology, 47,48 confocal microscopy, 49,50 and meibography 51,52 can serve as an additional tools for managing these patients.…”
Section: Investigationsmentioning
confidence: 99%
“…Although the exact mechanism is still not completely understood, there is ample evidence that posterior blepharitis is the result of an underlying cytokine and inflammatory-mediated process affecting both the meibomian glands and the ocular surface. 3,6 Fukushima et al, have shown in an animal model that experimental immune mediated blepharoconjunctivitis (EC) is dependent on an antigen recognized by T-cells. 11 This model demonstrates that T-cells are the prime orchestrator driving the infiltration of other inflammatory cells into the conjunctiva, as well as the upregulation of chemokines.…”
Section: Introduction P Osterior Blepharitis Is a Very Common Chronicmentioning
confidence: 99%
“…They may also have other associated symptoms of dry eye and may be plagued by blurred vision, gradual contact lens intolerance, as well as an increased risk of ocular surface damage and ocular infection. [1][2][3][4] Despite the high incidence of posterior blepharitis, there is currently no consistently effective treatment for this condition. Posterior blepharitis has traditionally been managed with eyelid hygiene, topical antibiotics, systemic antibiotics (specifically tetracycline), and corticosteroids.…”
Section: Introduction P Osterior Blepharitis Is a Very Common Chronicmentioning
confidence: 99%